Electro-spinning of cellulose acetate nanofibers/Fe/carbon dot as photoluminescence sensor for mercury (II) and lead (II) ions. (1st February 2020) - Ahmadian-Fard-Fini, Shahla; Ghanbari, Davood; Amiri, Omid; Salavati-Niasari, Masoud
Highlights: Carbon dots were prepared from hydrothermal-sonochemical procedures. Magnetic nano-fibers were synthesized by electro-spinning method. Carbon dots were synthesized on the magnetic nano-fibers. New photoluminescence sensor for detecting of mercury(II) and lead(II) was introduced. Abstract: The aim of this work is synthesis of magnetic and photoluminescence (PL) nano-fibers for detection of mercury (II) and lead (II) ions that are toxic and their detection are necessary. Prepared nanoparticles are controllable by external magnetic field, so their threat is much lesser than non-magnetic material. Firstly, iron nanoparticles were achieved with ball milling procedure and cellulose acetate (CA) nano-fibers were prepared by electro spinning procedure. Photoluminescence carbon dot were synthesized with citric acid (or lemon extract as green precursor). Fe nanoparticles were added to polymeric fibers and eventually, carbon dots were coated on the fibers by hydrothermal method. Evidence for carbon dot existence on the nanofibers is photo luminescence (blue color) under ultra-violet irradiation; results show reduction in PL intensity by enhancing of toxic heavy metal ions. A novel magnetic nano-fibers as a rapid test sensor for detecting of mercury(II) and lead(II) is presented.